A Delphi survey based construction and validation of test for oropharyngeal dysphagia in Indian neonates. (January 2021) - Krishnamurthy, Rahul; Balasubramanium, Radish Kumar; Kamath, Nutan; Bhat, Kamalakshi G.
Abstract: Background: SLPs have a crucial need to depend on comprehensive clinical swallowing assessments to determine the presence of dysphagia in neonates. A comprehensive clinical swallowing assessment that is ethnoculturally sensitive may help to identify the presence and severity of swallowing problems in neonates. Objective: The study aimed to construct and validate the contents of a test for oropharyngeal dysphagia in Indian neonates (TOD-IN). Method: The test for oropharyngeal dysphagia in Indian neonates (TOD-IN) was developed using the Delphi process. Five expert panelists served as participants; two rounds of electronic questionnaire-based survey was carried out to develop and validate the contents of TOD-IN. Results: Round one rendered descriptive data that was analyzed quantitatively and qualitatively. At the end of round one, panelists unequivocally agreed on the need for research to develop a validated assessment tool for dysphagia in Indian neonates. The second round dealt with establishing the face and content validity of the final version of TOD-IN. A unanimous consensus was obtained regarding the format, scoring system, and the construct of the final version of the tool. Conclusion: Practicing clinicians in India are met with several challenges such as resource constraints, limited infrastructure, increasing caseload, and a lack of trained workforce. We believe that inexperienced clinicians will benefit from the structured guidance provided by TOD-IN in a restrained resource context where prioritization of patients is the key. Further studies investigating the psychometric properties of TOD-IN are in progress.